Prime Minister Decree No. 3194 for the year 2022 Concerning the Rules Regulating The Insurance Covering the Civil Liability of Engineers and Contractors Against the Damage Occurring to a Third Party Due to a Total or Partial Collapse of Buildings and Establishments = قرار رئيس مجلس الوزراء رقم 3194 لسنة 2022 بشأن القواعد المنظمة للتأمين من المسئولية المدنية للمهندسين والمقاولين عن الأضرار التى تلحق بالغير بسبب ما يحدث بالمبانى والمنشآت من تهدم كلى أو جزئى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic